Clinical case of a patient undergoing radium-223 treatment following treatment with abiraterone acetate and enzalutamide - Jiménez Romero, M.E.; Díez Farto, S.; Navarro Serrato, J.C.; Canelón Castillo, E.; Revelo Cadena, I. (Experimental Oncology, 2018)
Objective: Over the last decade, significant advances have been made in the development of therapies for patients with metastatic castration-resistant prostate cancer. Abiraterone and enzalutamide were approved as treatments based on data supporting improved overall survival compared to placebo. Radium-223 became the first approved radiopharmaceutical which decreased skeletal-related events, palliated pain, and showed improved overall survival in symptomatic patients with castration-resistant prostate cancer and bone metastasis only. Materials and Methods: We present the case of an eighty-two year old man with metastatic castration-resistant prostate cancer who was treated with sequential therapy (abiraterone — enzalutamide — radium-223). The sequencing and treatment used for our patient was viable because of his clinical characteristics, which have allowed for longer survival time with an acceptable quality of life. These actions must be agreed on by the Multidisciplinary Tumour Board, in order to optimize the use of available courses of treatment. Results: The treatment of these patients is changing rapidly, but many questions remain regarding the optimal sequencing of the available drugs. Sequential or concomitant use of the next generation hormonal agents — abiraterone and enzalutamide — cannot currently be recommended. Data regarding the safety of concomitant abiraterone, enzalutamide or denosumab with radium-223 is reassuring and timely. However, we cannot advocate the general use of combined radium-223 therapy at this time, irrespective of prior therapy. Conclusion: A better understanding of active mechanisms, the genetic characteristics of each metastatic castration-resistant prostate cancer and the development of new prognostic and predictive biomarkers will help determine sequencing or different combination treatments for each individual patient. Key Words: castration-resistant prostate cancer, treatment sequence, abiraterone acetate, enzalutamide, radiopharmaceutic.